ANALISIS MEKANISME PENETAPAN HARGA JUAL DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS PADA PERCETAKAN ELLITE TANGGUL) - Zubadul Afiq, Ahmad (LPPM IAI Nazhatut Thullab, 2025)
In buying and selling or trading we know the term Price, determining Price is one of the important aspects in trading activities. Price becomes very important to note, considering that price determines whether or not a product will sell in trade. Wrong in determining the price will have fatal consequences in the products offered later. Price is the only element in trade that generates profit and income from the sale of goods and services, therefore the price set by the seller must be comparable to the value offered to consumers. The focus of the research includes: 1) How is the mechanism for determining the selling price at the Elit Tanggul photocopy and printing business? 2) How is the review of the selling price determination at the Elit Tanggul photocopy and printing business from an Islamic economic perspective. Research objectives: 1) To find out the mechanism of determining the selling price at the Tanggul Elite Photocopy and Printing. 2) To find out how the Islamic economic review of the selling price determination mechanism at the Tanggul Elite Photocopy and Printing. This study uses a descriptive qualitative method with the approach used in this study using a descriptive approach. Data collection techniques used are observation, interviews, and documentation. The data analysis technique of this study is a data analysis technique with an inductive method. The conclusion of this study is: 1) the selling price determination mechanism in thus printing company has a habit ofrounding prices. This is done to facilitate transactions and administration. 2) The determination of the selling price carried out by this business has been carried out optimally in accordance with the services that have been provided well, the goods sold are also of good quality. Therefore, this Elite photocopy and printing can also be said to have fulfilled the price determination in the perspective of Islamic economics, where the price determination carried out has been in accordance with economic principles. And in determining the price is done on the basis of mutual consent between the seller and the consumer so that no party feels disadvantaged.